Elevated triglycerides and low HDL cholesterol predict coronary heart disease risk in patients with stable angina. (20th July 2021) - Caselli, C; De Caterina, R; Smit, JEFF; El Mahdiui, M; Ragusa, R; Clemente, A; Sampietro, T; Clerico, A; Liga, R; Pelosi, G; Rocchiccioli, S; Parodi, O; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): The EVINCI study was supported by a grant from the European Union FP7-CP-FP506 2007 project (GA 222915). The SMARTool study was supported by a grant from the European Union H2020-PHC-30-2015 (GA 689068). This study was also partially supported by a grant from AMGEN (Protocol N. 20167781, 2017). Background. High triglycerides (TG) and low high-density lipoprotein cholesterol (HDL-C) characterize an atherosclerotic cardiovascular disease (CAD) risk condition defined as atherogenic dyslipidemia. Aim. To assess whether atherogenic dyslipidemia defined by TG/HDL-C ratio predicts CAD related outcomes in patients with stable angina, independently of other risk factors and treatments. Methods. We studied 355 patients (60 ± 9 y, 211m) with stable angina from the EVINCI Outcome study. Patients were characterized for clinical, bio-humoral and imaging profiles, managed clinically, and followed for 4.5 ± 0.9 years. A computed tomography angiography (CTA) coronary risk score was obtained at baseline in all patients, and at follow-up in 154 of them. The primary composite outcome was all-cause mortality and non-fatal myocardial infarction. CTA scan was repeated at follow-up in 154 patients to assess CAD progression. Results. The median value of TG/HDL-C ratio was 2.095 (2.079IQR). At baseline, the proportion of males, smoking, diabetes and metabolic syndrome, as well as circulating bio-markers of abnormal glucose metabolism and myocardial damage progressively increased across quartiles of TG/HDL-C ratio. The CTA score was significantly higher in the IV quartile of the TG/HDL-C ratio and both were the only independent predictors of the primary (CTA Score: HR 1.06, 95%CI 1.03-1.09, p = 0.001; TG/HDL-C IV quartile: HR 2.85, 95%CI 1.30-6.26, p < 0.01). In the 154 patients re-evaluated at follow-up, TG/HDL-C ratio associated cardio-metabolic disorder, systemic inflammation and CTA risk score progressed over time despite increased use of lipid-lowering drugs, anti-diabetics and other cardioactive medications and reduction in LDL-C levels. Conclusions. In patients with stable angina, the TG/HDL-C ratio expresses a cardio-metabolic atherogenic disorder which is progressive over time and is associated with CAD related outcomes independently of LDL-C levels and treatments.